1997
DOI: 10.1097/00000374-199706000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Alcohol-Metabolizing Genes Affects Drinking Behavior and Alcoholic Liver Disease in Japanese Men

Abstract: Alcohol is known to be mainly metabolized in the liver by alcohol dehydrogenase 2 (ADH2) and aldehyde dehydrogenase 2 (ALDH2), and cytochrome P-450IIEI. The purpose of this study was to clarify the role of polymorphism of these ethanol-metabolizing enzymes in drinking behavior and the progression of alcoholic liver disease among Japanese men. Polymorphism of the ADH2, ALDH2, and P-45IIEI genes were determined by polymerase chain reaction, followed by restriction fragment-length polymorphism analysis in 189 nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 0 publications
2
24
1
Order By: Relevance
“…The pooled results showed that c2c2 genotype was significantly associated with increased risk of ALD in Asians ( Table S2 ). These data were well consistent with many previous studies [14], [29], [48]. Another important finding was that a significant association between the CYP2E1 Pst I/Rsa I polymorphism and the ALD risk was also found in Caucasians (c1c2 vs. c1c1: OR = 1.63, 95%CI 1.05–2.53; c2c2/c1c2 vs. c1c1: OR = 1.58, 95%CI 1.04–2.42), although many pervious studies reported no association [11], [17], [19], [21], [23], [26], [27], [33], [36], [38].…”
Section: Discussionsupporting
confidence: 94%
“…The pooled results showed that c2c2 genotype was significantly associated with increased risk of ALD in Asians ( Table S2 ). These data were well consistent with many previous studies [14], [29], [48]. Another important finding was that a significant association between the CYP2E1 Pst I/Rsa I polymorphism and the ALD risk was also found in Caucasians (c1c2 vs. c1c1: OR = 1.63, 95%CI 1.05–2.53; c2c2/c1c2 vs. c1c1: OR = 1.58, 95%CI 1.04–2.42), although many pervious studies reported no association [11], [17], [19], [21], [23], [26], [27], [33], [36], [38].…”
Section: Discussionsupporting
confidence: 94%
“…ALDH2 gene polymorphism can determine flushing after ethanol ingestion. Flushing was reported in subjects homozygous for ALDH2*2/*2 and heterozygous for ALDH2*1/*2, but not in those homozygous for ALDH2*1/*1[47]. Concerning polymorphisms of the CYP2E1 gene, subjects heterozygous for the promoter alleles C1/C2 or homozygous C2/C2 are better able to metabolize alcohol, which might increase free radical generation and lipid peroxidation, and promote fatty change in the liver[9].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…There is an exception: the “flushing syndrome” variants at the aldehyde (ALDH) and alcohol (ADH) dehydrogenase loci in Asian individuals do provide genes of major effect in this population. Individuals with these gene variants are at lower risk for becoming dependent on alcohol than individuals with other genotypes (Chen et al, 1999) in Chinese (Thomasson et al, 1991; Chen et al, 1996), Korean (Shen et al, 1997), Japanese (Higuchi, 1994; Higuchi et al, 1994, 1995; Maezawa et al, 1995; Nakamura et al, 1996; Tanaka et al, 1997), and other populations (Luczak et al, 2002; Schuckit & Duby, 1982). Homozygous ALDH2*2 individuals are strongly protected from alcohol dependence (Higuchi, 1994; Higuchi et al, 1994).…”
Section: Failure To Document Evidence For Substance-dependence Genes mentioning
confidence: 99%